Understanding intra-regional transport: Competition in road transportation between Malawi, Mozambique, South Africa, Zambia, and Zimbabwe - Thando Vilakazi; Anthea Paelo (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
Efficient transport links are critical to enhancing the integration of markets in Southern Africa. This paper assesses the structure of markets, competition, and prices and costs of road transportation between urban hubs in Malawi, Mozambique, South Africa, Zambia, and Zimbabwe. Key findings are that certain routes, such as that between Lusaka and Johannesburg, have become more competitive over time and relative to benchmarks due to the availability of loads in each direction, improved efficiencies, and greater competitive rivalry between trucking firms from different countries. However, border delays and control of access to loads by large brokers continue to negatively affect competition and efficiency.
Keywords: D40; F15; L1; L50; L91; L92; 330; cross-border logistics; road transportation; Southern Africa; competition; regulation; regional integration